2004
DOI: 10.1007/s00453-004-1090-5
|View full text |Cite
|
Sign up to set email alerts
|

Automated Generation of Search Tree Algorithms for Hard Graph Modification Problems

Abstract: We present a framework for an automated generation of exact search tree algorithms for NP-hard problems. The purpose of our approach is twofold-rapid development and improved upper bounds. Many search tree algorithms for various problems in the literature are based on complicated case distinctions. Our approach may lead to a much simpler process of developing and analyzing these algorithms. Moreover, using the sheer computing power of machines it may also lead to improved upper bounds on search tree sizes (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…Encouraging results for the "simpler" but still NP-complete Closest 2-Leaf Power problem are obtained in [15,16] (where the problem is referred to as Cluster Editing).…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results for the "simpler" but still NP-complete Closest 2-Leaf Power problem are obtained in [15,16] (where the problem is referred to as Cluster Editing).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster Editing, parameterized by the number k of false positives and negatives, is FPT [3,9,10]. Furthermore, it has a polynomial-time 4-approximation algorithm but it does not admit a PTAS unless P = NP [14].…”
Section: Introductionmentioning
confidence: 99%
“…Parameterized complexity studies for Cluster Editing were initiated by Gramm et al [21] and have been further pursued in a series of papers [5,6,10,13,20,22,32,33]. A previously shown bound of O(1.92 k + n 3 ) for an n-vertex graph [20] can be improved by combining a linear-time problem kernelization algorithm [13] that yields an instance with O(k 2 ) vertices with the currently best claimed running time of O(1.82 k +n 3 ) [6] to get an algorithm with running time O(1.82 k +n+m), where m is the number of edges in the graph. Moreover, problem kernels, based on efficient data reduction rules, with only O(k) vertices are known [13,22], the best upper bound currently being 4k [22].…”
Section: Introductionmentioning
confidence: 99%
“…3 Using this characterization, one directly obtains fixed-parameter tractability [7] as well as a factor-3 polynomial-time approximation algorithm. Gramm et al [20] used an elaborate case distinction found with computer help to derive a search tree algorithm running in O(2.26 k m) time for an m-edge graph. This can be improved to O(2.08 k + n 3 ), n denoting the number of vertices, by using a straightforward reduction of unweighted Cluster Vertex Deletion to the 3-Hitting Set problem (transforming each induced P 3 into a three-element set) and employing a sophisticated algorithm for 3-Hitting Set [37].…”
Section: Introductionmentioning
confidence: 99%